Expediated modeling of burn events results (EMBER): A screening-level dataset of 2023 ozone fire impacts in the USzenodo - Heather Simon; James Beidler; Kirk R. Baker; Barron H. Henderson; Loren Fox; Chris Misenis; Patrick Campbell; Jeff Vukovich; Norm Possiel; Alison Eyth (Data in Brief)
The Expedited Modeling of Burn Events Results (EMBER) dataset consists of 36-km grid-spacing Community Multiscale Air Quality (CMAQ) photochemical modeling for the summer of 2023. For emissions, these simulations utilized representative monthly and day-of-week anthropogenic emissions from a recent year and preliminary day-specific 2023 fire emissions derived using BlueSky pipeline. The base model run simulated ozone concentrations across the contiguous US during Apr 11-Sep 29, 2023. Two zero-out model runs simulated ozone levels that would have occurred in the US (1) in the absence of fire emissions (“Zero Fires”) and (2) in the absence of only Canadian wildfire emissions (“Zero Canadian Fires”). Fire impacts on ozone were then estimated as the difference between ozone simulated in the base EMBER run compared to the ozone simulated in each of the zero out model runs. EMBER is presented as a screening level dataset due to the emissions limitations and the 36-km grid-spacing used in these simulations.